The Effect of Compensation, Work Environment, and Employee Engagement on Employee Performance at the Office of the Regional Financial and Revenue Management Agency (BPKPD) in Tana Toraja - Rice Ramme; Adriana Madya Marampa; Jens Batara Marewa (Pusat Riset dan Inovasi Nasional, 2026)
This study was conducted to analyze the influence of compensation, work environment, and employee engagement on employee performance at the Regional Financial and Revenue Management Agency (BPKPD) of Tana Toraja Regency, both partially and simultaneously. Data collection was carried out through questionnaires and documentation. The analysis method used was a quantitative approach with multiple linear regression techniques processed using the SPSS version 23 program. The results of simultaneous testing through the F test showed that compensation, work environment, and employee engagement together had a significant effect on employee performance. Furthermore, the results of the partial test (t test) showed that the compensation variable had a t-count value of 4.576 which was greater than the t-table of 2.002, so it had a positive and significant effect on employee performance. The work environment variable also showed a positive and significant effect with a t-count value of 2.141 which was greater than the t-table of 2.002. In addition, the employee engagement variable obtained a t-value of 3.187, which is greater than the t-table of 2.002, indicating a positive and significant influence on employee performance. Based on these results, it can be concluded that compensation, work environment, and employee engagement have a significant influence on employee performance.